KOMINFO DIGITAL LITERACY COUNSELING IN CIHAMPELAS VILLAGE, WEST BANDUNG REGENCY - Raden Agung Prio Wicaksono; Bogdan Ivanichyk (International Journal of Research in Community Services, 2022)
Disaster is a series of events that threaten and disrupt people's lives and livelihoods caused by both natural and/or non-natural factors as well as human factors, resulting in human casualties, environmental damage, property losses, and psychological impacts. In order to reduce the impact of those disasters, a Community Service Program (KKN) was held by providing community services regarding natural disaster mitigation training as an effort to minimize the impact of the risk of economic loss in the Citarum River watershed and digital literacy counseling to increase the distribution of literacy skills. digital community in Cihampelas Village, West Bandung Regency. The program is aimed at students of SMPN 1 Cihampelas which is geographically close to the Citarum watershed. The method used is the provision of material on both topics to students at SMPN 1 Cihampelas. Based on the results of the activity, it shows that students are successful in understanding the material that has been delivered.